P-46 Orthostatic hypotension and heart rate variability in the diagnosis of autonomic dysfunction in advanced cancer. (1st March 2017) - Leong, Chang Sheng; Barrett, Michelle; Joyce, David; Walsh, Declan
Abstract : Background: Autonomic dysfunction (AD) is common in advanced cancer. Cardiovascular signs include loss of heart rate variability (HRV) and later, orthostatic hypotension (OH). OH increases risk of falls and mortality. HRV is the time difference between successive heartbeats, measured as a standard deviation (SDNN). The mean SDNN found in normative population is 41.51ms (σ:26.28ms). OH is a decrease of ≥ 20mHg in systolic and/or 10mHg in diastolic blood pressure (BP) upon orthostatic stress. Persistence of OH (POH) is OH beyond three minutes Methods: This prospective, observational study aimed to identify prevalence of OH and POH, examine the relationship between autonomic symptoms (AS) and OH, and to ascertain whether OH and HRV are equivocally reliable for AD diagnosis. Consecutive ambulant adults attending day or in-patient hospice services were recruited. Interviews established demographics and AS. Objective tests for HRV and BP measurement were conducted. Postural symptoms were recorded during testing. Results: 22 (12 male, 10 female) participants were recruited. Median age was 70 (33–89). Eight had OH, three of these had POH. None with OH reported postural symptoms. Mean number of AS reported in non-POH group (n=5) and POH group (n=3) was 8 (σ:2.55) and 12 (σ:1.73) respectively. Mean SDNN (n=20) was 25.53 ms (σ:17.55ms). Association between OH and HRV (p=0.048, unpaired t test). Conclusions: OH was prevalent in this advanced cancer cohort and was associated with increased HRV. No association was found between AS and OH. Therefore, AS profile was not a useful tool for assessing AD. Active stand test was tolerated by all participants and could be considered for routine screening in advanced cancer. HRV screening may be an alternative for frailer patients